A novel pyrene-based two-photon active fluorescent dye efficiently excited and emitting in the 'tissue optical window (650–1100 nm)'. Issue 2 (4th November 2014) - Niko, Yosuke; Moritomo, Hiroki; Sugihara, Hiroyuki; Suzuki, Yasutaka; Kawamata, Jun; Konishi, Gen-ichi
Abstract : We synthesized a novel pyrene-based A–π–A dye that can be excited and fluoresce efficiently in the 'tissue optical window'. Abstract : The development of two-photon (TP) active fluorophores remains an important issue. Dyes that can be excited and fluoresce efficiently in the 'tissue optical window' (650–1100 nm) are especially in demand to maximize the underlying performance of two-photon fluorescence microscopy (TPFM) as an advanced optical technique. Ideally, such dyes would be compatible with the 1050 nm femtosecond fibre laser, which has recently been developed as an inexpensive excitation source to make the TPFM technique universal. In this work, we designed and synthesized a novel pyrene-based acceptor–π–acceptor (A–π–A) dye, PY, which exhibited outstanding properties such as bright fluorescence ( λ em = 650 nm and Φ FL = 0.80) and a large two-photon absorption cross-section (1100 GM (1 GM = 10 −50 cm 4 per photon per molecule) at 950 nm and 380 GM at 1050 nm) in the tissue optical window. In living mitochondria, PY provided more sensitive microscopic images than current dyes and showed great potential to be a building block of TP active fluorescent probes for the 1050 nm fibre laser. We believe that the exceptional properties ofPY will be extended to other fluorescent probes through further chemical modification.